Synthesis of inherently helical nanofibers: Effects of solidification of electrified jet during electrospinning - Yoon, Jihyun; Myung, Jun Ho; Kim, Yong‐Min; Jeon, Seung‐Yeol; Sun, Jeong‐Yun; Yu, Woong‐Ryeol (Journal of applied polymer science, 2022)
In this paper, a helical fiber was fabricated through electrospinning by increasing the vapor pressure of the solvent, increasing the conductivity of the polymer solution and forming an uneven electrical field distribution around the jet. Fiber morphology during electrospinning of a dielectric polymer solution was observed to dramatically change from straight to helical due to rapid solidification of the jet as vapor pressure of the solvent increased. A similar effect was observed with conductive solutions prepared by adding large amounts of metal ion to the polymer solution. The addition of metal ion induced strong electrical stresses, causing the electrified jet to rapidly solidify in the early stage of electrospinning. Simulations revealed that the jet near the nozzle tip was subject to a strong electrical field due to increased charge density. The thickness of the emerging fiber was rapidly reduced with fast and simultaneous solidification, resulting in helical nanofibers. In addition, by using the asymmetric spinnerets, an uneven electric field distribution around jet was generated, maximizing the fiber curvature and increasing the helical fiber ratio.